2018
DOI: 10.1177/0265532218775758
|View full text |Cite
|
Sign up to set email alerts
|

The impact of national standardized literacy and numeracy testing on children and teaching staff in remote Australian Indigenous communities

Abstract: All educational testing is intended to have consequences, which are assumed to be beneficial, but tests may also have unintended, negative consequences (Messick, 1989). The issue is particularly important in the case of large-scale standardised tests, such as Australia's National Assessment Program-Literacy and Numeracy (NAPLAN), the intended benefits of which are increased accountability and improved educational outcomes. The NAPLAN purpose is comparable to that of other state and national 'core skills' testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 51 publications
2
27
0
1
Order By: Relevance
“…The preferred language of the younger generations in this community, the mixed language Gurindji Kriol, is not commonly spoken outside the communities of Kalkaringi and Dagaragu, and so does not have a broader socioeconomic reach than Gurindji. Our findings are consistent with many remote Indigenous communities in Australia in which English is not the first language of most students (Macqueen et al 2018). In Australia, education in Indigenous communities is almost always conducted in English, even when English not commonly spoken in the day-to-day interactions in the community.…”
Section: The Effects Of Education In English and Exposure To Gurindjisupporting
confidence: 89%
See 2 more Smart Citations
“…The preferred language of the younger generations in this community, the mixed language Gurindji Kriol, is not commonly spoken outside the communities of Kalkaringi and Dagaragu, and so does not have a broader socioeconomic reach than Gurindji. Our findings are consistent with many remote Indigenous communities in Australia in which English is not the first language of most students (Macqueen et al 2018). In Australia, education in Indigenous communities is almost always conducted in English, even when English not commonly spoken in the day-to-day interactions in the community.…”
Section: The Effects Of Education In English and Exposure To Gurindjisupporting
confidence: 89%
“…In Australia, education in Indigenous communities is almost always conducted in English, even when English not commonly spoken in the day-to-day interactions in the community. Furthermore, in common with many other Anglophone countries, high-stakes educational testing in literacy and numeracy has been introduced, partly justified as a means to reduce Indigenous disadvantage by ensuring competency in English (Allendorf 2017;Macqueen et al 2018;McCarty 2009;Ryan and Whitman 2013;Wyman et al 2010). In Australia, USA, and Canada, where rates of Indigenous language loss have been the most dramatic, the results of nationwide tests for educational attainment, conducted in English, have been used to reduce support for bilingual education (Combs and Nicholas 2012;Devlin 2011;Wyman et al 2010).…”
Section: The Effects Of Education In English and Exposure To Gurindjimentioning
confidence: 99%
See 1 more Smart Citation
“…If school staff "desire to be ranked highly" (Thompson, 2013, p. 82), then NAPLAN and My School might contribute to increased commitment to the competitive "logic of neoliberalism" (Giroux, 2011, p. 8) and a potential corresponding erosion of commitment to social justice. Cumming et al (2016) and McQueen et al (2018) note that different groups of students are affected differently by NAPLAN. Drawing on data from interviews with school leaders and teachers, Cumming et al (2016, p. 128) note "principals' .…”
Section: Naplan and My Schoolmentioning
confidence: 99%
“…The study suggested to provide more resources to both the teachers and students to enhance the LLN skills in the early stage of education life. In another recent paper [5], the authors discussed impact of NAPLAN test in remote Australian indigenous communities.…”
Section: Introductionmentioning
confidence: 99%